Effect of fennel (Foeniculum vulgare Mill.) and coriander (Coriandrum sativum L.) on microbial quality and sensory acceptability of frozen paratha - Rosli, N. A.; Azilan, N. A.; Mahyudin, Nor Ainy; Mahmud Ab Rashid, N. K.; Meon, F. N. S.; Ismail, Z.; Chern, P. E.; Kanasan, S. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Fennel (Foeniculum vulgare Mill.) and coriander (Coriandrum sativum L.) are known to possess good antimicrobial properties. In the present work, spice-infused frozen parathas were formulated to investigate the effect of fennel and coriander on microbial (aerobic mesophilic bacteria, yeast and mould, and Bacillus cereus) reduction and sensory acceptability of frozen paratha throughout the storage at -18°C. The present work was also aimed at determining the relationship between spice concentrations and storage durations on microbiological quality of the samples. Fennel and coriander seed powder were used at concentrations of 2, 4 and 6% of wheat flour (w/w). The microbiological analysis was performed by total plate count, yeast and mould count, and Bacillus cereus count after 9, 12 and 15 weeks of storage. Sensory evaluation was conducted using hedonic scales at the end of storage durations. Results showed that spice infusion in frozen paratha significantly delayed the growth of aerobic mesophilic bacteria, yeasts and moulds, and Bacillus cereus during storage. The lowest log count was demonstrated by coriander at 6% in total plate count (3.85, 3.90 and 3.91 log10 CFU/g), and yeast and mould count (2.54, 2.59 and 2.60 log10 CFU/g) after 9, 12 and 15 weeks, respectively. Bacillus cereus was not detected throughout the storage durations. Fennel exhibited minimum activity against Bacillus cereus with no significant difference on log count reduction when compared with control. Coriander showed the highest decrease in both total plate count and Bacillus cereus count during the storage duration. Sensory evaluation result indicated that control sample exhibited the highest preference over all attributes when compared with fennel and coriander. Coriander-infused paratha was slightly darker in colour due to high concentration of 6%. Fennel yielded the lowest score in terms of taste among all samples. Fennel and coriander showed no significant difference for sensory acceptability. Overall, all frozen parathas were in good quality after 15 weeks of frozen storage. It can thus be concluded that fennel and coriander can be used as potential natural preservatives to inhibit the growth of microorganisms in paratha during frozen storage. Nevertheless, the optimum spice concentration should be determined to minimise the effects on the sensory attributes.